Implementation of the Mimicry-Memorization Method through flashcards in learning Arabic vocabulary - Desy Abidatus Sholihah; Umi Hanifah (Nurul Jadid University, 2025)
Arabic vocabulary mastery is a critical factor in developing students’ language competence and communication skills. This study aimed to examine the implementation of the Mimicry-Memorization method assisted by flashcards to enhance Arabic vocabulary learning. The research employed a qualitative phenomenological case study involving eighth-grade students, an Arabic teacher, and the school principal. Data were collected through participant observation, in-depth interviews, and documentation, then analyzed using interactive data analysis and triangulation to ensure validity. Findings revealed that integrating Mimicry-Memorization with flashcards increased students’ motivation, fostered interactive classroom participation, and improved vocabulary retention, as evidenced by worksheets, quizzes, and classroom activities. The study’s novelty lies in combining auditory imitation, structured repetition, and visual stimuli to create a holistic learning approach. Practically, the findings provide guidance for teachers to design engaging, student-centered vocabulary lessons. The research implies that multimodal strategies can enhance language acquisition and support long-term retention in Arabic learning.